The relationships of preservice teachers’ dispositions and noticing of technology-integrated mathematics teaching activities - Hsieh, Feng-Jui; Wang, Ting-Ying; Hsieh, Chia-Jui; Chu, Chi-Tai (ZDM, 2025)
This study explores the relationship between preservice teachers’ dispositions and their noticing of learning objectives and pedagogical opportunities supported by technology integration, building on the PID model. A k-means cluster analysis of 87 preservice teachers identified three disposition groups: all-objective , future-oriented objective , and traditional objective groups . The study examined noticing across three classroom scenarios, each representing a different level of preservice teachers’ familiarity with the mathematical teaching topic and technology-integrated instructional approaches in the Taiwanese teaching context. Results showed that the future-oriented objective group had a higher noticing percentage for 21st-century skills and attitudes, while the traditional objective group had a lower noticing percentage in these perspectives. The traditional objective group was more likely to notice task-level opportunities when the vignette content aligned with typical classroom instruction but less so when the content was less conventional. In contrast, the future-oriented objective group was more likely than the others to notice a range of pedagogical opportunities, particularly at the subject and classroom levels.